ANALYSIS THE IMPACTS OF RISKS IN THE USE OF ICT SYSTEMS ON THE PERFORMANCE OF SERVICES PROVIDED BY A BANKING COMPANY - Nikitha Salsabila Kirana; Stefan A. Schenke (Diponegoro Journal of Accounting, 2020)
This study aims to answer the main question by learning and analyzing broadly about the risks of the use of ICT systems in Mandiri Bank and also investigating the performance of services provided by this company. Further, There is a limitation which is about the technical risks that are excluded on this study.             Based on the results of this study, the main risk measure that can be applied to mitigate the impacts of the use of ICT systems risks in Mandiri Bank is the implementation of ISO 31000:2018 guidance to their operational risk model. And the suggestion for this research besides implementing ISO 31000:2018 is they should always listen to recommendations that come from their internal and external stakeholders who has the same goals to help Mandiri Bank overcome the effects of risks in the use of ICT systems.             However, in the end it can be considered from these analyses that Mandiri Bank already has a good performance of services that they give to the customers by preventing from the impacts of the use of ICT systems risks properly.